DEVELOPMENT OF THE COMPOSITION AND TECHNOLOGY OF CAPSULES OF DRY EXTRACT OF ANTI-INFLAMMATORY COLLECTION (Eureka Journal of Physical and Chemical Research, 2026)
This paper presents the results of research into the development and optimization of a technology for producing capsules containing a dry extract of an anti-inflammatory herbal mixture consisting of chamomile, rose hips, and oak bark. The composition of the mixture was substantiated based on an analysis of the pharmacological properties of each component and experimental confirmation of the content of biologically active substances.The dry extract was obtained by aqueous-alcoholic extraction ( 70 % ethanol) followed by spray drying, resulting in a stable powder with optimal physicochemical properties and a high content of total flavonoids (approximately 1.0% in terms of rutin ) and phenolic compounds (up to 6.7%). To create the capsule form, the composition of the excipients was optimized using five formulation options; the option including microcrystalline cellulose, anhydrous lactose, sodium CMC, colloidal silicon dioxide, and magnesium stearate was recognized as the best . This mixture ensured high fluidity, a bulk density of 0.55 g/cm³, an angle of repose of 32°, and dosing uniformity (RSD ≤ 1.7%).The encapsulation technology utilized direct dry filling into HPMC size 00 capsules, eliminating thermal exposure to heat-labile components. The resulting capsules met pharmacopoeial requirements for disintegration (≤ 12 min), moisture content, dosage uniformity, and release rate (Q₃₀ ≥ 85%). Testing confirmed the stability of the drug for 24 months. The results demonstrate the feasibility of creating a standardized, technologically reproducible, and biopharmaceutically effective herbal dosage form.
Keywords: Anti-inflammatory collection, dry extract, technology, plant raw materials, excipients, dosage form, technological properties, capsule.